The Representation of Chinese Characters in Kevin Kwan’s Crazy Rich Asians (2013) - Antonio Winatian (Universitas Pendidikan Indonesia (UPI), 2019)
Crazy Rich Asians (2013) is a best-selling novel depicting the life of Chinese characters who were born and grew up in Singapore and America respectively. Throughout their life, they interacted with Chinese as well as American culture which made them culturally hybrid characters. Thus, this study aims to analyze how Chinese characters are represented in the novel and the meaning behind the representation within the qualitative approach and textual analysis method. Using the theory of representation (Hall, 1997) and hybridity (Bhabha, 1994), this study reveals that the Chinese characters are represented through their thought, behavior, and language which inclined towards American culture. It is found that Rachel and Nick, despite their Chinese ethnicity, are represented to adopt and uphold American culture while also maintaining a few aspects of Chinese culture. Rachel adopts and chooses American culture consciously while maintaining her Chinese culture subconsciously. On the other hand, Nick is portrayed to uphold and maintain both American and Chinese cultures by choice throughout the novel. Furthermore, the analysis of this study indicates the effort of the author to challenge and subvert the existing Chinese stereotypes in literature namely yellow peril and model minority by utilizing the characters’ hybridity. The characters are shown to interact and negotiate with the new culture within the “Third Space of Enunciation” where all presumed characteristics and perceptions are nullified. By negotiating the cultures, they invalidate the notion of pure and fixed culture which is glorified by the stereotype of Chinese. Keywords: American culture, Chinese culture, hybridity, representation, stereotype